A multiphase model for tissue construct growth in a perfusion bioreactor - O'Dea, Reuben D.; Waters, Sarah L.; Byrne, Helen M. (Oxford University Press, 2010)
The growth of a cell population within a rigid porous scaffold in a perfusion bioreactor is studied, using a three phase continuum model of the type presented by Lemon et al. (2006, Multiphase modelling of tissue growth using the theory of mixtures. J. Math. Biol., 52, 571–594) to represent the cell population (and attendant extracellular matrix), culture medium and porous scaffold. The bioreactor system is modelled as a two-dimensional channel containing the cell-seeded rigid porous scaffold (tissue construct) which is perfused with culture medium. The study concentrates on (i) cell-cell and cell-scaffold interactions and, (ii) the impact of mechanotransduction mechanisms on construct composition.